Allostatic load, unhealthy behaviors, and depressive symptoms in the Hispanic Community Health Study/Study of Latinos. (December 2021) - Rodriquez, Erik J.; Coreas, Saida I.; Gallo, Linda C.; Isasi, Carmen R.; Salazar, Christian R.; Bandiera, Frank C.; Suglia, Shakira F.; Perreira, Krista M.; Hernandez, Rosalba; Penedo, Frank; Talavera, Gregory A.; Daviglus, Martha L.; et al.
Abstract: Background: The Environmental Affordances Model (EAM) proposes that the effects of chronic stress on depression are moderated by unhealthy behaviors and race/ethnicity. The unique social structures and contexts of Hispanics/Latinos in the U.S. may influence such relationships. This study evaluated whether unhealthy behaviors weakened the relationship between allostatic load, a measure of chronic stress, and future elevated depressive symptoms among Hispanic Community Health Study/Study of Latinos participants. Methods: Longitudinal data (2008–2011 and 2014–2017) from 11, 623 participants were analyzed. The exposure was allostatic load, an index of twelve established biomarkers categorized using clinically relevant cut points, at Visit 1. Elevated depressive symptoms were operationalized as a score of ≥10 (out of 30) on the CES-D 10 at Visit 2. An index of unhealthy behaviors, with one point each for cigarette smoking, excessive/binge drinking, sedentary behavior, and poor diet quality at Visit 1, was examined as an effect modifier. Multivariable logistic regression, in the overall sample and among Mexicans specifically and adjusted for demographic characteristics and elevated depressive symptoms at Visit 1, was used to model allostatic load, unhealthy behavior index (range: 0–4), and their interaction in relation to elevated depressive symptoms at Visit 2. Results: Overall, greater allostatic load was associated with higher odds of elevated depressive symptoms after at least 6 years (aOR = 1.06, 95% CI = 1.01, 1.10). Overall, individuals with greater allostatic load and an unhealthy behavior index = 1, compared to those with an unhealthy behavior index = 0, had lower odds of elevated depressive symptoms at follow-up (aβ = −0.065, 95% CI = −0.12, −0.007). Conclusions: The relationship between chronic stress and depression was partially moderated among Hispanics/Latinos who engaged in unhealthy behavior, which may have reduced their risk of elevated depressive symptoms given more chronic stress. Highlights: Unhealthy behaviors may reduce the effect of chronic stress on depressive symptoms. Allostatic load, unhealthy behaviors, and elevated depressive symptoms were studied. Longitudinal association between allostatic load and elevated depressive symptoms. One unhealthy behavior interacted with greater allostatic load among Latinos. Findings partially support the Environmental Affordances Model among Latinos.